National Danish surveillance of invasive clinical Haemophilus influenzae isolates and their resistance profile - Slotved, Hans-Christian; Johannesen, Thor Bech; Stegger, Marc; Dalby, Tine; Fuursted, Kurt (Frontiers in Microbiology, 2023)
Introduction: This study aimed to investigate the epidemiology, serotype distribution, phenotypical antibiogram, and molecular resistance gene characteristics of invasive Haemophilus influenzae infections in Denmark from 2014 to 2022. Additionally, the potential impact of outdoor temperature and COVID-19 restrictions on the epidemiology of H. influenzae was assessed. Materials and Methods: Invasive H. influenzae isolates were received from patients with positive culture results from cerebrospinal fluid, blood, or other sterile sites. Sample data were obtained from the Danish laboratory surveillance system/MiBa database, and whole-genome sequencing (WGS) was performed on the isolates. The incidence rates and distribution of H. influenzae cases were analyzed, and antibiotic susceptibility were assessed. Results: A total of 1,007 invasive H. influenzae cases were identified, with serotyping conducted for 752 (74.7%) isolates. The median incidence per year of H. influenzae was 2.0 cases per 100,000, with the highest incidence in 2014 and the lowest in 2020. The majority of H. influenzae isolates were non-typeable H. influenzae (NTHi), while the most prominent serotypes were serotype f followed by serotype b. Bacteremia cases accounted for the majority (88.6%) of occurrences, although meningitis cases showed an increasing trend during the time period. The age group 85+ exhibited the highest incidence. The implementation of COVID-19 preventive interventions in 2020 resulted in a significant reduction in H. influenzae incidence, which returned to pre-COVID levels in 2021. A negative correlation was observed between monthly H. influenzae cases and outdoor temperature. An overall level of genetic beta-lactamase resistance of 26.3% was observed divided into 10.6% beta-lactamase-positive ampicillin-resistant (gBLPAR), 13.6% beta-lactamase-negative ampicillin-resistant (gBLNAR) and 2.1% beta-lactamase-positive amoxicillin clavulanate-resistant (gBLPACR). Other non-beta-lactam resistance traits were detected in 7.6% of isolates (primarily aminoglycoside-modifying enzymes). Conclusion: The overall incidence of H. influenzae in Denmark returned to stable levels after the COVID-19 epidemic, with NTHi strains dominating. The COVID-19 preventive interventions led to a major reduction in incidence. A significant negative correlation between the incidence of H. influenzae and temperature was observed. The study revealed an overall genetic beta-lactam resistance rate of 26.3%, and the concordance between genotypic and phenotypic beta-lactam resistance was high (98.2%).